1985
DOI: 10.1093/infdis/151.2.314
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Localization of T Lymphocytes in Disseminated Coccidioidomycosis

Abstract: Immunohistochemical techniques using monoclonal antibodies to T lymphocyte subpopulations were used to characterize further the granulomas of disseminated coccidioidomycosis. Skin biopsy specimens from patients with disseminated coccidioidomycosis were studied and compared with tissues from experimentally infected mice. In human skin biopsy specimens and infected mouse tissues, discrete granulomata were seen in which T lymphocytes formed a peripheral mantle surrounding central aggregates of macrophages. This u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…In particular, Modlin and colleagues' data from humans principally consisted of skin biopsies from patients with disseminated coccidioidomycosis (13). The finding of a positive ratio of CD4 ϩ to CD8 ϩ lymphocytes and the production of IFN-␥ in the mantle region of granulomata in the present study are consistent with a reaction favoring a strong cellular immune response.…”
Section: Cd25supporting
confidence: 85%
“…In particular, Modlin and colleagues' data from humans principally consisted of skin biopsies from patients with disseminated coccidioidomycosis (13). The finding of a positive ratio of CD4 ϩ to CD8 ϩ lymphocytes and the production of IFN-␥ in the mantle region of granulomata in the present study are consistent with a reaction favoring a strong cellular immune response.…”
Section: Cd25supporting
confidence: 85%
“…Patients with tuberculoid leprosy, tuberculosis and pulmonary coccidioidomycosis have shown a particular pattern of T lymphocyte distribution in the granulomas. As the host response in these diseases is partly effective against the pathogen, the granulomatous pattern with T helper/inducer cells and macrophages in the center of the lesion and suppressor/cytotoxic cells at the periphery, suggests an in situ regulatory arrangement which promotes isolation and lysis of the etiologic agent [8][9][10].…”
Section: Resultsmentioning
confidence: 99%
“…Immunopathologic studies of other human granulomatous diseases have shown that the efficacy of the host response is related to the presence and distribution of T lymphocytes in the inflammation mounted to counteract the pathogen [8,10]. No similar work has been done on granulomas caused by P. brasiliensis . We have studied the number and distribution pattern of T lymphocyte subsets in granulomas observed in biopsy specimens from patients with paracoccidioidomycosis.…”
mentioning
confidence: 99%
“…Numerous studies have demonstrated that animals that lack T cells are more susceptible to infection with these fungi than are those with immunocompetent T cells Beaman et al 1979;Beck et al 1996;Gomez et al 1988;Hill and Harmsen 1991;Huffnagle et al 1991;Menacci et al 1994Menacci et al , 1996Modlin et al 1985;Mody et al 1993;Tewari et al 1978). Numerous studies have demonstrated that animals that lack T cells are more susceptible to infection with these fungi than are those with immunocompetent T cells Beaman et al 1979;Beck et al 1996;Gomez et al 1988;Hill and Harmsen 1991;Huffnagle et al 1991;Menacci et al 1994Menacci et al , 1996Modlin et al 1985;Mody et al 1993;Tewari et al 1978).…”
Section: Cellular Immunity (T-cell Mediated Immunity)mentioning
confidence: 99%